1993
DOI: 10.1016/1044-0305(93)80017-s
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear resonance effects during ion storage in a quadrupole ion trap

Abstract: Contributions of higher-order fields to the quadrupolar storage field produce nonlinear resonances in the quadrupole ion trap. Storing ions with secular frequencies corresponding to these nonlinear resonances allows absorption of power from the higher-order fields. This results in increased axial and radial amplitudes which can cause ion ejection and collision-induced dissociation (CID). Experiments employing long storage times and/or high ion populations, such as chemical ionization, ion-molecule reaction stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Moreover, the nonlinear fields are regarded as the main factor in the degradation of the ion trap performance. For instance, the resultant nonlinear effects, such as ion delay ejection [31,32], nonlinear resonance [33,34], and frequency shift [35,36], are considered to be harmful to the mass resolution, sensitivity, and mass accuracy, respectively. With the in-depth study, the nonlinear fields have been found to be beneficial and have the potential to break the performance barrier and develop new operation modes of the ion trap.…”
mentioning
confidence: 99%
“…Moreover, the nonlinear fields are regarded as the main factor in the degradation of the ion trap performance. For instance, the resultant nonlinear effects, such as ion delay ejection [31,32], nonlinear resonance [33,34], and frequency shift [35,36], are considered to be harmful to the mass resolution, sensitivity, and mass accuracy, respectively. With the in-depth study, the nonlinear fields have been found to be beneficial and have the potential to break the performance barrier and develop new operation modes of the ion trap.…”
mentioning
confidence: 99%
“…The nonlinear resonance potentially gives rise to the ion loss and the sensitivity degradation of the ion trap instruments [12][13][14][15][16]. It is meaningful to predict the rf working voltage (represented by the q value), at which the nonlinear resonance occurs.…”
Section: Resultsmentioning
confidence: 99%
“…The weight can increase to 10% or higher in some Paul trap geometrical variations [5], such as cylindrical [6] and rectilinear ion traps [7]. The nonlinear fields inevitably introduce a series of nonlinear effects into the ion motion, such as frequency shift [8][9][10], amplitude variation [11], nonlinear resonance [12][13][14][15][16], and thus have great impacts on the trap performance, in terms of mass resolution [8], mass accuracy [9], sensitivity [12], and tandem MS (MS/MS) efficiency [10,15], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a decrease in the parameter range for q z trapping ions). 21 The main resulting e †ects are the following : (i) erroneous m/z measurements which correspond to mass shifts,22 (ii) distortion of peak shapes23 and (iii) a loss of the higher m/z ions when the lower m/z ions are abundant. 20 IonÈion interactions also lead to large ion excursions away from the center of the ion trap and ions approach the end-caps in addition to the ring electrode.…”
Section: Introductionmentioning
confidence: 99%